Relation between opioid consumption and inclusion of opioids in 137 national essential medicines lists - Richards, GC; Aronson, JK; Heneghan, C; Mahtani, KR; Koshiaris, C; Persaud, N (BMJ Publishing Group, 2020)
Introduction Opioids are deemed essential medicines by the World Health Organization (WHO). However, many countries have inadequate access to them. Whether including opioids in national essential medicines lists (EMLs) influences national opioid consumption has not been evaluated.